A Case of Cauda Equina Injury Through an Anterior Abdominal Stab Wound. (11th January 2023) - Suddaby, Amelia V.; Yen, David
Abstract : This case study discusses a unique case of a cauda equina injury through an anterior abdominal stab wound that was missed on initial assessment in the trauma bay. The true nature of the injury was only discovered intraoperatively, despite preoperative clinical findings and imaging. A literature review was conducted, and only one other instance of anterior stab injury to the spine was reported. The purpose of this case study was to allow for earlier recognition of anterior transection injuries of the cauda equina and to highlight the importance of advanced imaging and exploratory surgery in cases of abdominal penetrating injuries presenting in conjunction with neurologic deficits.